CircNAPEPLD is expressed in human and murine spermatozoa and physically interacts with oocyte miRNAs. Issue 9 (2nd September 2019) - Ragusa, Marco; Barbagallo, Davide; Chioccarelli, Teresa; Manfrevola, Francesco; Cobellis, Gilda; Di Pietro, Cinzia; Brex, Duilia; Battaglia, Rosalia; Fasano, Silvia; Ferraro, Bruno; Sellitto, Carolina; Ambrosino, Concetta; et al.
ABSTRACT: Circular RNAs (circRNAs) have a critical role in the control of gene expression. Their function in spermatozoa (SPZ) is unknown to date. Twenty-eight genes, involved in SPZ/testicular and epididymal physiology, were given in circBase database to find which of them may generate circular transcripts. We focused on circNAPEPLDiso1, one of the circular RNA isoforms of NAPEPLD transcript, because expressed in human and murine SPZ. In order to functionally characterize circNAPEPLDiso1 as potential microRNA (miRNA) sponge, we performed circNAPEPLDiso1-miR-CATCH and then profiled the expression of 754 miRNAs, by using TaqMan® Low Density Arrays. Among them, miRNAs 146a-5p, 203a-3p, 302c-3p, 766-3p and 1260a (some of them previously shown to be expressed in the oocyte), resulted enriched in circNAPEPLDiso1-miR-CATCHed cell lysate: the network of interactions generated from their validated targets was centred on a core of genes involved in the control of cell cycle. Moreover, computational analysis of circNAPEPLDiso1 sequence also showed its potential translation in a short form of NAPEPLD protein. Interestingly, the expression analysis in murine-unfertilized oocytes revealed low and high levels of circNAPEPLDiso1 and circNAPEPLDiso2, respectively. After fertilization, circNAPEPLDiso1 expression significantly increased, instead circNAPEPLDiso2 expression appeared constant. Based on these data, we suggest that SPZ-derived circNAPEPLDiso1 physically interacts with miRNAs primarily involved in the control of cell cycle; we hypothesize that it may represent a paternal cytoplasmic contribution to the zygote and function as a miRNA decoy inside the fertilized oocytes to regulate the first stages of embryo development. This role is proposed here for the first time.